Словотвірні моделі та когнітивні механізми мережевої номінації (на матеріалі доменних імен новостворених веб-сайтів) - Столярова, М.О. (Центр наукових досліджень та викладання іноземних мов НАН України, 2008)
Статья посвящена исследованию лингвокреативной деятельности человека и особенностей номинативно-деривационных процессов образования доменных имён для новых веб-сайтов как взаимодействия языковых и внеязыковых факторов. В работе проанализированы основные словообразовательные модели, а также окказиональные способы словообразования, изучены когнитивные механизмы сетевой номинации, рассмотрены автоматически генерированные доменные имена. The article discusses human linguistic creativity and peculiarities of nominative derivational processes participating in creation of domain names for new websites. The paper analyzes productive ways of word formation, as well as nonce words, studies cognitive mechanisms of nomination on the Internet, offers an overview of automatically generated domain names and aims to determine the influence of language and extralanguage factors on the choice of a domain name.